Comparison of Quality and Microstructure of Strawberry Powders Prepared by Two Different Drying Methods: Low Temperature Drying with Convection Dryer and Vacuum Freeze Drying - Nishizono Masayo; Soreli Castro Issasi Cinthya; Mizukami Hiroyuki; Sasaki Mitsuru (Journal of Antioxidant Activity, 2022)
Convection dryers are the most affordable and most commonly used dryers for processing of agricultural products. However, since the temperature is high or the drying time is long, materials such as fruits and vegetables may turn brown and the nutrients deteriorate, therefore this method is not suitable for the production of dry powders for fruits and vegetables, which are expected to have bright colors and nutritional functions. Low temperature drying (LTD) has made it possible to produce strawberry dry powder with the equivalent functional components as powder by vacuum freeze drying (FD). In addition, the processing time is shorter and the cost is lower than vacuum FD. In this study, we demonstrate the superiority of LTD by comparing the quality and microstructure of strawberry powders produced by LTD and vacuum FD.
Keywords: Strawberry powder